2022
DOI: 10.1186/s12887-022-03201-9
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between vigorous physical activity and health care costs among adolescents: ABCD Growth Study

Abstract: Background The relationship between physical activity and health care costs among adolescents is not yet clear in the literature. Objective To analyze the relationship between physical activity and annual health care costs among adolescents. Methods The present sample was composed of 85 adolescents of both sexes with ages ranging from 11 to 18 years (mean age 15.6 ± 2.1). Health care costs were self-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Although the questionnaires used to assess both insufficient PA and sleep problems in our sample have been previously validated, widely used in epidemiological studies, and applied by trained researchers, the non-objective measures of PA and sleep may be considered relevant limitations. This aspect seems relevant because both the relationships between PA and sleep and between PA and costs seem to be affected by intensity and sleep patterns, 10 , 26 which are easier to measure using objective methods. Physiological pathways linking diet and sleep problems exist, such as synthesis of serotonin and melatonin, and thus, the absence of diet control constitutes a limitation of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Although the questionnaires used to assess both insufficient PA and sleep problems in our sample have been previously validated, widely used in epidemiological studies, and applied by trained researchers, the non-objective measures of PA and sleep may be considered relevant limitations. This aspect seems relevant because both the relationships between PA and sleep and between PA and costs seem to be affected by intensity and sleep patterns, 10 , 26 which are easier to measure using objective methods. Physiological pathways linking diet and sleep problems exist, such as synthesis of serotonin and melatonin, and thus, the absence of diet control constitutes a limitation of our study.…”
Section: Discussionmentioning
confidence: 99%
“…However, many recent studies showed positive psychosocial outcomes including many internal and external mental health and academic achievement (Breslin et al, 2023;Spruit et al, 2016). Moreover, vigorous PA has been known to improve or maintain health and lower health care cost of adolescents (Torres et al, 2022). Globally renowned institutions in PA and health such as American College of Sports Medicine and World Health Organization recommend moderate-to-vigorous physical activity (MVPA) of 60 minutes or more every day of the week.…”
Section: Discussionmentioning
confidence: 99%
“…Engaging in physical activity can be a challenge due to staying at home, however, it is possible and very important to stay active, because of social isolation. Not engaging in physical activity comes with health issues and financial costs (Su et al, 2020;Torres et al, 2022). An adequate physical activity is medically proven to help in preventing and managing noncommunicable diseases (NCDs), including heart disease, stroke, diabetes and several cancers.…”
Section: Introductionmentioning
confidence: 99%